IMPLEMENTASI KARAKTER CINTA TANAH AIR PADA KESENIAN TRADISIONAL JAWA INDONESIA - Hanifah Nuryani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This study aims to describe and interpret the implementation of the character of patriotism in traditional Javanese Indonesian art. This research method uses a qualitative descriptive approach with interviews, observations, field notes, and documentation as data collection techniques. The research unit is the principal, musical teacher, and students. Data validity test is done using triangulation of sources and techniques. Data were analyzed using the interactive model of Miles and Huberman. The results showed that (1) Javanese tradi-tional culture at SD N Grogol reflected the nationalism character which was implemented in musical extracurricular activities. (2)Careful planning and implementation of musical activities rou-tinely carried out every week forms the character of the nationalism in students, namely the atti-tude of respect and preserve the nation's culture. (3) Karawitan culture can provide role models that contain the value of the nationalism character and can be applied by students in life. This study concluded that the Javanese traditional culture at SDN Grogol reflected the nationalism character that is implemented in musical extracurricular activities.